THE USE OF PEER CHECKLIST IN TEACHING APPLICATION LETTER WRITING - Yosepha, Anjelina; Supardi, Iwan; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purposes of this research are to find out whether the use of Peer Checklist effective or not and to find out how effective the use Peer Checklist is in teaching an application letter writing to eleventh grade students of SMK LKIA in academic year 2014/2015. This research was conducted as pre-experimental research. The sample of this research was class XI KN1 which consists of 34 students. The data were collected by using pre-test and post-test through a written test. In the written test, the students were asked to write an application letter. The data were analyzed by using Effect Size (ES) formula. The finding shows that the effect of the treatment is 1.21 (≥ 1.00) or categorized as strong effect. Therefore, it was concluded that the use of peer checklist is effective in teaching the application letter writing. Keywords: Writing, Application Letter, Peer Checklist. Abstrak: Penelitian ini bertujuan untuk mengetahui apakah penggunaan Peer Checklist efektif atau tidak dan untuk mengetahui keefektifan penggunaan peer Checklist dalam pengajaran menulis surat lamaran pekerjaan terhadap siswa kelas XI SMK LKIA Pontianak tahun ajaran 2014/2015. Penelitian ini dilakukan dengan menggunakan metode pre-eksperimen. Sampel penelitian ini adalah siswa kelas XI KN1 yang terdiri dari 34 siswa. Data penelitian dikumpulkan melalui pre-test dan post-test dengan menggunakan tes tertulis. Data tersebut dianalisa dengan menggunakan rumus ES (tingkat efektivitas). Hasil penelitian menunjukkan bahwa efek dari pengunaan peer checklist adalah 1.21 (≥ 1.00) atau dikategorikan memiliki efek yang kuat. Dapat disimpulkan bahwa penggunaan peer checklist efektif dalam pengajaran menulis surat lamaran kerja. Kata Kunci: Menulis, Surat Lamaran pekerjaan, Peer Checklist.